Patterns of Research Effort and Extinction Risk of Marine Mammals in the Philippines - Tiongson, Angelico Jose C.; Utzurrum, Jean Asuncion; de la Paz, Manuel Eduardo L. (Frontiers in Marine Science, 2021)
Global marine mammal research is disproportionately lacking compared to terrestrial mammal research and is strongly biased toward populations in Europe, North America, New Zealand, and Australia. With high extinction risks facing marine mammals in the tropics, we sought to identify potential drivers of research effort and extinction risk evaluations for marine mammals in the Philippines as a model for tropical island nations with limited resources and research capacity. Using a bibliographic approach, we compiled all materials on marine mammal research in the Philippines from 1991 to 2020, which we categorized into eight thematic areas of research focus. We reviewed all materials based on their research focus to assess the current scientific knowledge of local marine mammal populations. Using a simple metric to calculate research effort allocation, we found that all marine mammal species in the Philippines receive inadequate research attention. Using generalized linear models, we analyzed the relationship of potential factors that drive research effort. The model with the lowest Akaike Information Criterion value suggests that frequency of marine mammal stranding incidents may influence an increase in research effort on marine mammals by providing access to biological specimens that would normally be difficult to obtain. Strandings are unfortunate events with often unclear causes, but they provide an opportunity to collect data from behaviorally cryptic animals in areas where financial constraints often hamper scientific progress. We also determined that a national Red List evaluation was predicted by increased research effort. Maximizing local research using all materials from strandings and building research capacity may be an alternative to expensive field-based methods to increase knowledge on local marine mammal populations.